Experimental verification of column at extreme temperature - Abdul Ghani, Badri (Faculty of Mechanical Engineering, 1996)
Experimental studies have been carried out to predict the fire resistance of protected I-shaped steel insulated with ceramic fibre. The steel section selected were W250-80 and W310-158. The experimental results are compared with those obtained using the mathematical models develop by the same authors. The results indicate that the model is capable of predicting the fire.